Genomic analyses of 238 seed plants reveal the evolutionary mechanisms driving specialization of F3H, ANS, and FLS in flavonoid biosynthesis - Liu, Siqi; Zhou, Zeyu; Wang, Weibin; Jia, Cheng; Li, Dawei; Hao, Tingting; Chen, Yue (Frontiers in Plant Science, 2026)
IntroductionFlavonoid metabolism innovation is critical for seed plants’ terrestrial adaptation. Three key 2-oxoglutarate-dependent dioxygenase (2ODD) families—F3H, ANS, FLS—underpin flavonoid biosynthesis, but their evolutionary diversification mechanisms remain unclear.MethodsComprehensive analyses were performed across 238 seed plant genomes, including phylogenetic/collinearity analyses, conserved motif detection, duplication-type classification, selection pressure assessment, and Brassica napus promoter/expression profiling.ResultsThese families originated from a common ancestral gene (ancestor X) and diversified via multiple duplications (TRD/WGD as primary drivers). Their evolution aligns with the EAC model, with subfunctionalization resolving ancestral multifunctionality. Structural conservation and lineage-specific motif variations support functional differentiation, and purifying selection predominates.DiscussionOur findings clarify the molecular evolutionary mechanisms of flavonoid pathway diversification, providing novel insights into the origin of flavonol and anthocyanin biosynthesis in seed plants.